Culturally Tailored Smoking Cessation for Arab American Male Smokers in Community Settings: A Pilot Study - Linda Haddad; Jacqueline Corcoran (SAGE Publishing, 2013)
Tobacco use is a serious public health problem among Arab Americans with limited English proficiency. The main goal of this study was to develop a culturally-tailored and linguistically-sensitive Arabic-language smoking cessation program. A secondary goal was to evaluate the feasibility of recruiting Arab Americans through a faith-based community organization which serves as a neighborhood social center for the city of Richmond's Arab Americans. Eight first-generation Arab American men aged 20 years and above completed the three-month program. There was general agreement of the following: (1) each stage of the five-stage cessation program could be improved; (2) several glaring errors could be easily corrected; and (3) minor variation among the various countries-of-origin of participants could lead to a few changes in the program with respect to the use of some colloquial terms. The results suggest that it is possible to reach smokers from Arab American communities with a tailored Arabic language smoking cessation program. The findings of this report will be used as the basis for a large-scale intervention study of a culturally and linguistically sensitive cessation program for Arab American ethnic groups.